FEATURES OF RESISTANCE LITERATURE IN THE PALESTINIAN LITERATURE: GHASSAN KANAFANI’S WORKS AS EXAMPLES - Heba A. S. Wadi (Universitas Airlangga, 2020)
This paper attempts to explore resistance in Palestinian literature and its impacts on various aspects of colonized people's lives and interpretations in the field of literature. The paper focuses on Ghassan Kanafani's perspectives for the simple reason that he is recognized as the one who laid the foundation of resistance literature in Palestine. Ghassan Kanafani (1941-2008) was one of the lofty figures who believed in the importance of the word and transformed it into a resistance weapon. Kanafani is a well-known contemporary Palestinian writer and genius author who made a great contribution to the literature of Palestinian resistance against colonialism and the Israeli occupation. He loved his country with all of his heart. As the results, his novels served as a luminous flame to awaken the subconscious and remind the patriots of the Palestinians or all the Arabs of their usurped rights. Therefore, his novels and short stories also spilled like thunder on the Zionist forces. They stirred human emotions and shocked the minds of the international community.This paper attempts to explore resistance in Palestinian literature and its impacts on various aspects of colonized people's lives and interpretations in the field of literature. The paper focuses on Ghassan Kanafani's perspectives for the simple reason that he is recognized as the one who laid the foundation of resistance literature in Palestine. Ghassan Kanafani (1941-2008) was one of the lofty figures who believed in the importance of the word and transformed it into a resistance weapon. Kanafani is a well-known contemporary Palestinian writer and genius author who made a great contribution to the literature of Palestinian resistance against colonialism and the Israeli occupation. He loved his country with all of his heart. As the results, his novels served as a luminous flame to awaken the subconscious and remind the patriots of the Palestinians or all the Arabs of their usurped rights. Therefore, his novels and short stories also spilled like thunder on the Zionist forces. They stirred human emotions and shocked the minds of the international community.